A STUDY ON IMPACT OF WORK FROM HOME ON EMPLOYEES PERFORMANCE AND PRODUCTIVITY OF IT INDUSTRIES WITH REFERENCE TO PUNE CITY - Khalate, Santosh; Bansode, Ulhas; Prajapati, Pooja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The idea of remote work, or working from home, has been increasingly popular in recent years. During the COVID-19 pandemic, remote work has undoubtedly emerged as one of the most widely utilized strategies to reduce unemployment, maintain societal functions, and protect the public from the virus. Nevertheless, the effects of working from home on employee productivity and performance remain unclear, existing research on this topic is scattered and varies across different contexts. Thus, the aim of this study is to conduct a systematic review of the effects of Work from Home on employee productivity and performance. This study mainly focuses on the how employees were generating output by working remotely and how it can affect their performance and productivity and effect on their personal life.